John of Salisbury - Nederman, Cary J. (Medieval and Renaissance texts and studies, 2005)
Life and career -- Early life and education (1115/1120-1147) -- In the service of Canterbury (1148-1156) -- Author and administrator (1157-1161) -- The Becket dispute (1162-1170) -- Final years (1171-1180) -- Writings -- Entheticus de dogmate philosophorum -- Policraticus -- Metalogicon -- Historia pontificalis.